2022
DOI: 10.3389/fendo.2021.802632
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Traditional Semen Parameters, Sperm DNA Fragmentation, and Unexplained Recurrent Miscarriage: A Systematic Review and Meta-Analysis

Abstract: Several studies have explored the relationship among traditional semen parameters, sperm DNA fragmentation (SDF), and unexplained recurrent miscarriage (RM); however, the findings remain controversial. Hence, we conducted a meta-analysis to explore the relationship among traditional semen parameters, SDF, and unexplained RM. Multiple databases, including PubMed, Google Scholar, MEDLINE, Embase, Cochrane Library, Web of Science, and China National Knowledge Infrastructure (CNKI), were searched to identify relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…The rate of blastocyst aneuploidy in the low sperm motility group was significantly higher than that in the normal sperm motility group (46.7% vs 33.7%, P<0.05). Dai’s research showed that couples with unexplained RM had significantly decreased levels of total motility compared with couples without recurrent miscarriage, but no differences were observed in the semen volume, sperm concentration, and total sperm count between couples with and without recurrent miscarriage ( 15 ). This is exactly consistent with the conclusions of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of blastocyst aneuploidy in the low sperm motility group was significantly higher than that in the normal sperm motility group (46.7% vs 33.7%, P<0.05). Dai’s research showed that couples with unexplained RM had significantly decreased levels of total motility compared with couples without recurrent miscarriage, but no differences were observed in the semen volume, sperm concentration, and total sperm count between couples with and without recurrent miscarriage ( 15 ). This is exactly consistent with the conclusions of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a high sperm DNA fragmentation index (DFI) of sperm increases the early miscarriage rate ( 13 , 14 ), and embryonic chromosomal abnormality is one of the main causes of early pregnancy loss. A recent meta-analysis also showed that couples with unexplained recurrent miscarriage had significantly increased levels of sperm DFI and significantly decreased levels of total motility compared with couples without recurrent miscarriage ( 15 ). Therefore, we hypothesized that male factors are also closely related to embryo aneuploidy.…”
Section: Introductionmentioning
confidence: 97%
“…Sperm DNA fragmentation (SDF) is considered one of the main factors involved in infertility (Panner Selvam et al, 2021). Sperm cells with damaged DNA or poor quality may obstruct embryonic development, raising the risk for miscarriage and foetal development complications (Dai et al, 2021). Therefore, over the years, SDF has become a biomarker for assessing male fertility status (Esteves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Therefore, there are some limitations in evaluating male fertility only based on sperm motility, sperm density, sperm normal shape rate, sperm survival rate, and so on in semen analysis. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Therefore, there are some limitations in evaluating male fertility only based on sperm motility, sperm density, sperm normal shape rate, sperm survival rate, and so on in semen analysis. [6,7] Sperm DNA is the carrier of genetic material. Sperm chromosome abnormality or DNA damage caused by any factor will reduce male fertility potential and even cause male infertility.…”
Section: Introductionmentioning
confidence: 99%